2010
DOI: 10.3109/17518423.2010.499889
|View full text |Cite
|
Sign up to set email alerts
|

Telepractice in the assessment and treatment of individuals with autism spectrum disorders: A systematic review

Abstract: Results suggests telepractice is a promising service delivery approach in the treatment of individuals with ASD that warrants additional research. Guidelines for practitioners and potential directions for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
162
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(174 citation statements)
references
References 27 publications
6
162
0
4
Order By: Relevance
“…The articles included in this review were most commonly rated as "Weak" or "Borderline Adequate" on the Evaluative Method, indicating that they lacked key indicators of methodological quality. This finding replicates earlier findings by Boisvert et al (2010) who similarly found that research relating to telehealth support for people with ASD had key methodological flaws. Only five studies in the current review were rated as "Adequate" (one relating to trainee outcomes: Knowles et al 2017; four relating to client outcomes: Lindgren et al 2016;Machalicek et al 2009b;Neely et al 2016;Wacker et al 2013a), and one as "Strong" (relating to client outcomes: Gibson et al 2010).…”
Section: Methodsological Quality Of Evidence Basesupporting
confidence: 90%
See 1 more Smart Citation
“…The articles included in this review were most commonly rated as "Weak" or "Borderline Adequate" on the Evaluative Method, indicating that they lacked key indicators of methodological quality. This finding replicates earlier findings by Boisvert et al (2010) who similarly found that research relating to telehealth support for people with ASD had key methodological flaws. Only five studies in the current review were rated as "Adequate" (one relating to trainee outcomes: Knowles et al 2017; four relating to client outcomes: Lindgren et al 2016;Machalicek et al 2009b;Neely et al 2016;Wacker et al 2013a), and one as "Strong" (relating to client outcomes: Gibson et al 2010).…”
Section: Methodsological Quality Of Evidence Basesupporting
confidence: 90%
“…There is currently no known review focusing solely on behavior analytic research, with previous reviews focusing on other fields (e.g., psychotherapy Gros et al 2013; palliative care, Kidd et al 2010; speech pathology, Mashima and Doarn 2008), or more broad training interventions for parents of children with disabilities (e.g., Meadan and Daczewitz 2015). Boisvert et al (2010) recently reviewed literature relating to the use of telehealth for providing support to individuals with an Autism Spectrum Disorder (ASD), including five studies focusing solely on ABA techniques. The review included articles where support was provided in relation to behavior and educational goals to teaching staff and parents, or psychological support provided directly to individuals with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…A signifi cant history of the use of technology to provide healthcare and therapeutic assessment and intervention exists to provide successful models for practitioners to adapt to their communities and organisations (Behl, Houston, Guthrie, & Guthrie, 2010;Boisvert, Lang, Andrianopoulos, & Boscardin, 2010). Early pioneers in healthcare and rehabilitation services identifi ed ethical and legal issues, including the professional responsibilities necessary for quality teleintervention services (Cohn & Cason, 2012).…”
Section: A Preview Of the Teleintervention Modelmentioning
confidence: 99%
“…[12][13][14][15] The ADOS is a critical part of ASD assessment in adults, but there is a lack of available clinical expertise to meet need, 16 especially in poorly served areas. A possible solution is the use of technology for remote assessment.…”
mentioning
confidence: 99%